Armenia : Promoting Productive Employment - World Bank (Washington, DC, 2013)
This paper examines labor market outcomes in Armenia and their impact on poverty. The outcomes are of considerable concern: relatively few persons of working age are employed, and many of those who are employed have low-productivity jobs. The problem is not only high unemployment, but also low labor force participation. The main factor behind the low employment/population ratio is weak labor demand and the scarcity of productive job opportunities. This paper begins in section one by discussing the main labor market challenges in Armenia, before focusing on unemployment in section two. Section three analyzes the nature of employment and jobs, while section four examines wage determination and structure. Section five then evaluates the relationship between individuals' and households' labor market status and poverty. Finally, section six concludes with policy implications of the analysis. In order to reach the 60 percent employment rate Armenia would need to create an additional 166,000 jobs. This will lead to a 14 percent increase in employment, and to some decrease in unemployment. More jobs need to be created to absorb the growing labor surplus. This implies growing unemployment and a decline in the already low employment rate. Accelerating the pace of job creation is thus one of the main social challenges facing policymakers in Armenia. Furthermore, it is important that in the longer term, wage growth does not exceed labor productivity growth. Otherwise, competitiveness of the Armenian economy could suffer due to a growth in the unit labor cost, which in turn, can have a detrimental effect on job creation.